Modulation of Type I Interferon Responses to Influence Tumor-Immune Cross Talk in PDAC - Cattolico, Carlotta; Bailey, Peter; Barry, Simon T. (Frontiers in Cell and Developmental Biology, 2022)
Immunotherapy has revolutionized the treatment of many cancer types. However, pancreatic ductal adenocarcinomas (PDAC) exhibit poor responses to immune checkpoint inhibitors with immunotherapy based trials not generating convincing clinical activity. PDAC tumours often have low infiltration of tumour CD8+ T-cells and a highly immunosuppressive microenvironment. These features classify PDAC as immunologically “cold”. However, the presence of tumour T-cells is a favorable prognostic feature in PDAC. Intrinsic tumour cell properties govern interactions with the immune system. Alterations in tumour DNA such as genomic instability, high tumour mutation burden and/or defects in DNA damage repair are associated with responses to both immunotherapy and chemotherapy. Cytotoxic or metabolic stress produced by radiation and/or chemotherapy can all act as potent immune triggers, and prime immune responses. Damage or stress mediated activation of nucleic acid sensing pathways trigger Type-I interferon (IFN-I) responses that activate innate immune cells, natural killer cells, promote maturation of dendritic cells and stimulate adaptive immunity. While PDAC exhibits intrinsic features that have the potential to engage immune cells, particularly following chemotherapy, these immune-sensing mechanisms are ineffective. Understanding where defects in innate immune triggers render the PDAC tumour-immune interface less effective, or how T-cell function is suppressed will help develop more effective treatments and harness the immune system for durable outcomes. This review will focus on the pivotal role played by IFN-I in promoting tumour cell – immune cell cross talk in PDAC. We will discuss how PDAC tumour cells bypass IFN-I signaling pathways and explore how these pathways can be co-opted or re-engaged to enhance therapeutic outcome